2018
DOI: 10.3390/en12010076
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Shaped ( A g − F e 3 O 4 / H 2 O ) Hybrid Nanofluid

Abstract: The main concern is to explore an electro-magneto hydrodynamic (EMHD) squeezing flow of ( A g − F e 3 O 4 / H 2 O ) hybrid nanofluid between stretchable parallel Riga plates. The benefits of the use of hybrid nanofluids, and the parameters associated to it, have been analyzed mathematically. This particular problem has a lot of importance in several branches of engineering and industry. Heat and mass transfer along with nonlinear thermal radiation and chemical reaction effects have also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 48 publications
(131 reference statements)
0
12
0
Order By: Relevance
“…where,K denotes the thermal conductivity of a host fluid. Furthermore, by following the mixture formula, the Bruggeman model can be upgraded for the hybrid nanofluid, which can be wri en as [13,20,35]:…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…where,K denotes the thermal conductivity of a host fluid. Furthermore, by following the mixture formula, the Bruggeman model can be upgraded for the hybrid nanofluid, which can be wri en as [13,20,35]:…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The equation for mass conservation (Equation (18)) is automatically verified; however, the Equations (19), (20), (22) and (25), can be wri en, in the dimensionless form, as:…”
Section: Problem Formulation In Curvilinear Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Siddiqui et al [9] reported the squeezed flow bounded by two parallel plates. Recently, Ahmed et al [10] reported the flow of hybrid nanofluid squeezed between two Riga plates. They used numerical technique for mathematical treatment of the hybrid model, and ensured the validity of the scheme by comparing the results with existing once in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth theme of research that emerged can be referred to as "Flow with micro-and nano-scale features". This includes the following papers: There are two papers dealing with microbubbles present in the flow [14,15], a nanofluids application [16], ferromagnetic fluid behaviour [17] and a particle deposition problem [18].…”
mentioning
confidence: 99%